Chinese Generic Cities and Their Urban Futures - Lau, Sunnie Sing-Yeung; González Martínez, Paula (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
Despite the fact that China’s urban growth has been widely studied and discussed over the last decades, this paper intends to offer a particular and most recent vision of the present scenario. From our Hong Kong and Mainland architectural experiences, being fully involved in the cases that we are about to describe and trying to avoid generalizing, we aim to redefine somewhat of a repetitive reality and the implications of it in the near future because of two major dangers: 1. The new cities become generic without proper assimilation process to illustrate locality and cultural identity; 2. Built large scale development losses adaptability to changes into other program once obsolete.
Keywords: China; generic cities; urban growth; cultural identity; large scale